Clustering of Integrin αIIb-β3Differently Regulates Tyrosine Phosphorylation of pp72syk, PLCγ2 and pp125FAKin Concanavalin A-stimulated Platelets - Torti, Mauro; Festetics, Enrico Tolnai; Bertoni, Alessandra; Sinigaglia, Fabiola; Balduini, Cesare (Thrombosis and Haemostasis, 1999)
Tyrosine phosphorylation of the non-receptor tyrosine kinases pp72sykand pp125FAKand of the γ2 isoform of phospholipase C (PLCγ2) in human platelets stimulated with the lectin Concanavalin A was investigated. Concanavalin A induced the rapid tyrosine phosphorylation of pp72sykand PLCγ2 with a similar kinetics, while tyrosine phosphorylation of pp125FAKoccurred in a later phase of platelet activation. When compared with other platelet agonists, Concanavalin A revealed to be at least as potent as collagen in inducing tyrosine phosphorylation of PLCγ2 and pp125FAK, while tyrosine phosphorylation of pp72sykinduced by the lectin was much stronger than that induced by thrombin or collagen. Concanavalin A-induced tyrosine phosphorylation of pp72syk, PLCγ2 and pp125FAKwas not dependent on platelet aggregation as it occurred normally even in the absence of sample stirring and when fibrinogen binding to integrin αIIb-β3was inhibited by the peptide RGDS. Tyrosine phosphorylation of pp72syk, PLCγ2 and pp125FAKrequired the binding of the lectin to the platelet surface, but was not observed in platelets treated with succinyl-Concanavalin A, a derivative of the lectin that interacts with the same receptors but does not promote clustering of membrane glycoproteins. Moreover, the aggregation-independent tyrosine phosphorylation of pp125FAKand pp72sykinduced by Concanavalin A required the expression of integrin αIIb-β3on the platelet surface as it was strongly inhibited in platelets from patients affected by Glanzmann thrombasthenia. By contrast, tyrosine phosphorylation of PLCγ2 occurred normally also in thrombasthenic platelets stimulated with Concanavalin A. These results demonstrate that, even in the absence of aggregation, the clustering of integrin αIIb-β3induced by Concanavalin A on the platelet surface directly promotes tyrosine phosphorylation of pp72sykand pp125FAKand provide further evidence that the oligomerization of the fibrinogen receptor promoted by its natural ligand during platelet aggregation may be responsible for the tyrosine phosphorylation of these proteins induced by physiological agonists.